Yes Homo: Gay Influencers, homonormativity, and queerbaiting on YouTube. Issue 5 (3rd September 2019) - Abidin, Crystal
ABSTRACT: Considering the 'It Gets Better' network of videos and recent reversal of censorship on queer content, this paper looks at how gay Influencers on YouTube perform intimacy, care, and attachment with their followers alongside practicing activism. Specifically, it considers what happens when the discursive activism of gay networks become entangled with the publicity-driven initiatives of Influencer commerce, and how in-routes into diversity and inclusivity are undermined by intersectional marginality and networked power of the status quo. This paper focuses on networks that centre around three gay-identifying Australian YouTubers: Troye Sivan, Jake Bley, and Fraser Green, considering their posts and comments from followers between 2013 and 2017, with a heavier focus on Sivan's videos. All statistics presented were last recorded in August 2017. A grounded theory approach was adopted in the content analysis of data from digital participant observation. The paper observes the entanglement of brand capital, relational intimacies, and activism performed by gay Influencers, as they use their status to promote discursive activism, constitute networks around their internet celebrity, and grow their careers.